Caspase-mediated cleavage of the exosome subunit PM/Scl-75 during apoptosis - Schilders, Geurt (BioMed Central, 2007)
Recent studies have implicated the dying cell as a potential reservoir of modified autoantigens that might initiate and drive systemic autoimmunity in susceptible hosts. A number of subunits of the exosome, a complex of 3'→5' exoribonucleases that functions in a variety of cellular processes, are recognized by the so-called anti-PM/Scl autoantibodies, found predominantly in patients suffering from an overlap syndrome of myositis and scleroderma. Here we show that one of these subunits, PM/Scl-75, is cleaved during apoptosis. PM/Scl-75 cleavage is inhibited by several different caspase inhibitors. The analysis of PM/Scl-75 cleavage by recombinant caspase proteins shows that PM/Scl-75 is efficiently cleaved by caspase-1, to a smaller extent by caspase-8, and relatively inefficiently by caspase-3 and caspase-7. Cleavage of the PM/Scl-75 protein occurs in the C-terminal part of the protein at Asp369 (IILD369↓G), and at least a fraction of the resulting N-terminal fragments of PM/Scl-75 remains associated with the exosome. Finally, the implications of PM/Scl-75 cleavage for exosome function and the generation of anti-PM/Scl-75 autoantibodies are discussed.